Exploring the Temperature‐Dependent Structural Evolution of Mechanically Synthesized Na3PS4 Solid Electrolyte through In Situ X‐Ray Diffraction - Sergio Federico Mayer; Marta Mirolo; Alisson Andrea Iles Velez; Ove Korjus; Emmanuelle Suard; Laureline Lecarme; Jean‐Baptiste Ducros; Claire Villevieille (Small Structures)
Exploring the potential of sodium‐based materials is of utmost importance, especially for next‐generation solid‐state batteries. Herein, Na3PS4 thiophosphate solid electrolyte is focused on. While its tetragonal α phase is initially studied for Na solid‐state batteries, the impact of heat treatment and the phase transitions of amorphous and semicrystalline polymorphs obtained by mechanochemical synthesis remains poorly understood. The structural evolution is evaluated as function of the temperature of amorphous and semicrystalline Na3PS4 polymorphs obtained by mechanochemical processes. Both samples are heat‐treated during an in situ synchrotron X‐ray diffraction measurement, and multiple phase transitions are detected, some of them being irreversible. A novel and abundant orthorhombic intermediary phase is observed when the heat treatment is performed on the amorphous sample. The ionic conductivity of both amorphous and semicrystalline samples undergoes significant enhancement after heat treatment, reaching 0.09 and 0.16 × 10−3 S cm−1, respectively. This research sheds light on the thermal dynamics of Na3PS4 polymorphs, providing valuable insights into their crystallization processes, especially in the amorphous‐to‐cubic transition. The discovered intermediate phases underscore the potential for further advancements in sodium‐based solid‐state battery technologies.